Evaluating the Impact of Secant Piles on Retaining Wall Safety at Lapangan Merdeka Medan - Juwita Nasution, Adinda; Fadlan, Rahmatsyah; Berutu, Habib (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study investigates the effectiveness of integrating secant piles into retaining wall systems for basement construction, with a specific focus on the Medan Merdeka Square Revitalization Project. As part of a major redevelopment effort in a historically significant urban area, ensuring the structural stability of basement walls is essential to protect both the site and surrounding infrastructure. Secant pile walls, composed of overlapping reinforced concrete piles, offer enhanced lateral resistance and groundwater control compared to conventional retaining structures. The research evaluates wall performance before and after the application of secant piles through geotechnical analysis and engineering stability assessments. The methodology includes determining lateral earth pressure using Rankine’s Theory and conducting stability checks against overturning, sliding, and bearing capacity failure. Soil characteristics, earth pressure coefficients, and relevant safety factors are analyzed to understand how the combined secant pile–reinforced concrete system distributes loads and improves structural performance. Construction methods and sequencing are also considered to ensure minimal disruption to the heritage environment. The results indicate that the retaining wall with added secant piles meets all required stability criteria: sliding resistance is safe, overturning potential is negligible, and bearing capacity is adequate to support the applied loads. Additionally, the recorded deflection value of 0.8 remains within acceptable limits, confirming the structural suitability of the design. Overall, the incorporation of secant piles significantly enhances the stability and reliability of the basement retaining wall, making it appropriate for long-term implementation in the revitalization project.